(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The halal industry has developed rapidly globally one of which is in Indonesia. According to the 2021 census, the majority of Indonesia's population is predominantly Muslim, namely around 237.53 million people. As one of the countries with a majority Muslim community, the state must have concern in increasing the potential of the halal industry. Therefore, the halal industry should be a driving force in driving global economic growth. The development of the halal industry in Indonesia, especially in the province of Papua, there are still problems and challenges that must be faced, one of the problems in the halal industry sector in Papua, especially in the city of Jayapura, is the development of Halal food which is still minimal due to a lack of knowledge about halal certification in products marketed. This type of research is using a qualitative method with a case study approach which has stages of observation, interviews and documentation of MSME actors with the aim of getting maximum results. The results of this study are product halal certification which is carried out to provide a sense of security to consumers and increase product value. The results of further research are that halal certification provides added value, namely cleanliness, halalness and product safety for consumption